Mentale rum og kohærens - Knoth, Tine Woergaard; Bernhardt, Lise (HERMES - Journal of Language and Communication in Business, 2001)
This article sets out to describe the relationship between mental spaces and text coherence. When a reader interprets a text he mentally divides it into smaller parts, so-called mental spaces. The question is how texts cohere in spite of the fact that the mental spaces in principle work against text coherence because of their dividing function. The article will show that text reference helps to establish text coherence but only the macro level makes the text fully cohere.